Confirmation of the high cumulative incidence of thrombotic complications in critically ill ICU patients with COVID-19: An updated analysis. Issue 191 (July 2020) - Klok, F.A.; Kruip, M.J.H.A.; van der Meer, N.J.M.; Arbous, M.S.; Gommers, D.; Kant, K.M.; Kaptein, F.H.J.; van Paassen, J.; Stals, M.A.M.; Huisman, M.V.; Endeman, H.
Abstract: Introduction: We recently reported a high cumulative incidence of thrombotic complications in critically ill patients with COVID-19 admitted to the intensive care units (ICUs) of three Dutch hospitals. In answering questions raised regarding our study, we updated our database and repeated all analyses. Methods: We re-evaluated the incidence of the composite outcome of symptomatic acute pulmonary embolism (PE), deep-vein thrombosis, ischemic stroke, myocardial infarction and/or systemic arterial embolism in all COVID-19 patients admitted to the ICUs of 2 Dutch university hospitals and 1 Dutch teaching hospital from ICU admission to death, ICU discharge or April 22nd 2020, whichever came first. Results: We studied the same 184 ICU patients as reported on previously, of whom a total of 41 died (22%) and 78 were discharged alive (43%). The median follow-up duration increased from 7 to 14 days. All patients received pharmacological thromboprophylaxis. The cumulative incidence of the composite outcome, adjusted for competing risk of death, was 49% (95% confidence interval [CI] 41–57%). The majority of thrombotic events were PE (65/75; 87%). In the competing risk model, chronic anticoagulation therapy at admission was associated with a lower risk of the composite outcome (Hazard Ratio [HR] 0.29, 95%CI 0.091–0.92). Patients diagnosed with thrombotic complications were at higher risk of all-cause death (HR 5.4; 95%CI 2.4–12). Use of therapeutic anticoagulation was not associated with all-cause death (HR 0.79, 95%CI 0.35–1.8). Conclusion: In this updated analysis, we confirm the very high cumulative incidence of thrombotic complications in critically ill patients with COVID-19 pneumonia.